2010
DOI: 10.1002/ijc.24988
|View full text |Cite
|
Sign up to set email alerts
|

Promoter demethylation and chromatin remodeling by green tea polyphenols leads to re‐expression of GSTP1 in human prostate cancer cells

Abstract: Epigenetic silencing of gluthathione-S-transferase pi (GSTP1) is recognized as being a molecular hallmark of human prostate cancer. We investigated the effects of green tea polyphenols (GTPs) on GSTP1 re-expression and further elucidated its mechanism of action and long-term safety, compared with nucleoside-analog inhibitor of DNA methyltransferase (DNMT), 5-aza-2 0 -deoxycitidine. Exposure of human prostate cancer LNCaP cells to 1-10 lg/ml of GTP for 1-7 days caused a concentration-and time-dependent re-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
135
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(139 citation statements)
references
References 44 publications
3
135
0
1
Order By: Relevance
“…3). Epigenetic regulation, including DNA methylation and histone modification, is an important process in cancer development, and the epigenetic regulatory activity of certain dietary phytochemicals with cancer chemopreventive potential has been demonstrated, including curcumin (21), EGCG (20), and genistein (44). We have previously shown that the expression of Nrf2 can be attenuated by DNA CpG methylation in both the prostate tumor tissue of TRAMP mice and tumorigenic TRAMP C1 cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…3). Epigenetic regulation, including DNA methylation and histone modification, is an important process in cancer development, and the epigenetic regulatory activity of certain dietary phytochemicals with cancer chemopreventive potential has been demonstrated, including curcumin (21), EGCG (20), and genistein (44). We have previously shown that the expression of Nrf2 can be attenuated by DNA CpG methylation in both the prostate tumor tissue of TRAMP mice and tumorigenic TRAMP C1 cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…As a putative cancer chemotherapeutic agent derived from dietary constituents, GTPs have been suggested to play a significant role in the resistance of a variety of cancers including liver, breast, prostate, lung, and skin by numerous studies of cell cultures and animal models (Luo et al, 2006;Thangapazham et al, 2007;Lu et al, 2008;Pandey et al, 2010). GTPs are the major active component group of green tea, accounting for 30%-42% of the dry weight of the solids in brewed green tea, and are mainly composed of catechins (Khan and Mukhtar, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular modeling and docking studies supported the binding of EGCG to DNMT3B in HeLa cells [108]. EGCG (5-20 μM) or Pholyphenon E® (1-10 μg/mL) treatments of different PCa cell lines, have determined a dose-and time-dependent reexpression of GSTP1 enzyme concomitantly with the down-regulation of DNMT1 [41,106]. The reexpression of GSTP1, induced by treatment with EGCG or Polyphenon E® may be, at least in part, responsible for the quenching of free radicals species and reduction of DNA damage associated with oxidative stress [41].…”
Section: Epigenetic Mechanismsmentioning
confidence: 88%
“…Cancer development involves a complex multistep process caused and associated to many genetic insults that include genetic mutation as well epigenetic alteration [105]. Many tumor suppressor and receptor genes have been reported to be hypermethylated and transcriptionally silenced during the development of various human cancers, including PCa [106]. The major epigenetic mechanisms that control gene expression are DNA methylation, histone modifications and expression of noncoding regulatory micro RNA (miRNAs).…”
Section: Epigenetic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation